2021
DOI: 10.1002/aenm.202101413
|View full text |Cite
|
Sign up to set email alerts
|

Metal Phosphides Embedded with In Situ‐Formed Metal Phosphate Impurities as Buffer Materials for High‐Performance Potassium‐Ion Batteries

Abstract: As anodes for metal-ion batteries, metal phosphides usually suffer from severe capacity degradation because of their huge volume expansion and unstable solid electrolyte interphase (SEI), especially for potassium-ion batteries (PIBs). To address these issues, this study proposes amorphous phosphates acting as buffer materials. Ten types of metal phosphide composites embedded with in situ-formed amorphous phosphates are prepared by one-step ball milling using red phosphorus (RP) and the corresponding metal oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 82 publications
5
16
0
Order By: Relevance
“…Furthermore, the EDS mappings (Figure f) show that Ag, P, and K elements are homogeneously distributed over the anode material. A similar K + -storage mechanism in metal phosphides was also reported. ,, On the basis of the above results, we conjecture the reaction mechanism that AgP 2 decomposes into Ag nanocrystals and K 3 P after discharge in the first cycle and the reversible reaction is K 3 P ↔ P + K. After cycling, the Ag has no volume change because it does not react with K + . However, the reversible reaction of K 3 P ↔ P + K has a significant volume change.…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, the EDS mappings (Figure f) show that Ag, P, and K elements are homogeneously distributed over the anode material. A similar K + -storage mechanism in metal phosphides was also reported. ,, On the basis of the above results, we conjecture the reaction mechanism that AgP 2 decomposes into Ag nanocrystals and K 3 P after discharge in the first cycle and the reversible reaction is K 3 P ↔ P + K. After cycling, the Ag has no volume change because it does not react with K + . However, the reversible reaction of K 3 P ↔ P + K has a significant volume change.…”
Section: Resultssupporting
confidence: 81%
“…In our recent work, we demonstrated that metal phosphides prepared by using metal oxides exhibit enhanced cycling stability in ethylene carbonate/diethyl carbonate (EC/DEC)‐based electrolyte. [ 9 ] Zinc phosphate is inactive to K‐ion in nature, and pure ZnO, when used as the raw material at the molar ratio of ZnO to P of 2:3, introduced the maximum mass percentage of zinc phosphate of 37.7 wt%, which would reduce the theoretical specific capacities of the zinc phosphide composites. Therefore, we optimized the content of zinc phosphate by controlling the proportion of Zn, ZnO, and P raw materials to keep a balance between the cycling stability and high specific capacity of zinc phosphide.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the amorphization of zinc phosphide increased with the increase in the proportion of zinc phosphate and carbon and were consistent with our previous findings, which were obtained by using pure ZnO to prepare completely amorphous zinc phosphide. [ 9 ] As shown in Figure 1d–i, a high‐resolution transmission electron microscope (HRTEM) was also employed to confirm the existence of zinc phosphide. In ZnP 2 @ZPO(10) (Figure 1d), the measured interplanar spacings of 0.284 and 0.204 nm matched with the (114) and (214) lattice planes of ZnP 2 phase, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…can undergo alloying reactions with K metal in organic KIBs to achieve efficient K storage. [106][107][108][109][110] These elements have attracted widespread attention for their low operating voltages and high capacities. However, it is rarely reported in AKIBs.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%